THE TRANSFORMATION OF TROPICAL BUILDING IN SOUTHEAST ASIA - Mandarin Guntur (Jurusan Arsitektur UPR, 2016)
The tropical building was built for living such as a traditional building but today vernacular building is just a part of the building style or a decoration. People are not lived in a traditional building anymore. They are not also expressing their entire life in this building. Especially, for people who are lived in urban area. When modern era comes (after 1920s), all aspect of the traditional living has left behind. Nowadays, not only the style of building has changed but also the concept of building construction has moved to the other methods (Goldblum, 2014). All buildings using glass as a wall to separate and forming the room, we cannot see the different buildings in Jakarta, Kuala Lumpur, Manila, Singapore and Bangkok. Therefore, in the era of global warming (after 1990), the tropical building expression has suddenly transformed into a new expression of architecture (Goldblum, 2014). The study is aimed at comparing the expression of the tropical building through the style, composition, type, morphology and place before 1920, between 1920 and 1990, and after 1990, in order to know how the change of building features in Southeast Asia, sequentially which is now toward sustainability design. Knowing the tropical building expression that afordable for the urban poor in Southeast Asia and how it will be implemented in current condition. In addition, this study is also intended to get a new consideration regarding concept of tropical building design, particularly in several cities of Southeast Asia. The last, to observed an impact of climate change on the building features in Southeast Asia. The analysis of study used an exploring design situation methods (divergence) and the evaluation methods (convergence) in order to know how the expression of building. It is clear that this research resulted a serial of tropical architecture expression (on the buildings design) from time to time in the cities of Southeast Asia and how it was transformed or sublimed into a new conception due to the climate change impact on it which is now toward sustainability. How a tropical building expression which is affordable and sustainable for the urban poor in Southeast Asia. Also how a Building material (building features) which can adapt to the impact of climate change in Southeast Asia and the last is a new consideration for tropical architectural design studies and design methods of architecture in Southeast Asia which is impacted by climate change.